LITERASI KESEHATAN UNTUK MELATIH KEMANDIRIAN ANAK USIA 4–5 TAHUN DI TK PUTRA II SERANG-BANTEN - Laila Luzaini Wafa; Siti Khosiah; Fahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Independence is one of the important developmental aspects that needs to be trained from the age of 4–5 years, since at this age children begin to be able to carry out various basic activities without fully depending on adults. In reality, however, many young children are still accustomed to receiving excessive assistance from parents or caregivers, so their independence has not developed optimally. This study aims to describe the implementation of health literacy in training the independence of children aged 4–5 years and to identify teachers' strategies in supporting the development of that independence at TK Putra II Serang, Banten. The study used a descriptive qualitative approach with data collected through observation, interviews, and documentation involving children in Group A, classroom teachers, and the school principal. Data were analyzed through data reduction, data display, and conclusion drawing, and their validity was tested through source and technique triangulation. The results show that health literacy at TK Putra II Serang is implemented through habituation of clean and healthy living behaviors such as handwashing, disposing of waste properly, maintaining personal and environmental cleanliness, an "ant operation" cleaning activity, the 5M waste-management activity, and periodic health programs conducted in cooperation with the local community health center. These habituations consistently shape children's independence, evident in their ability to care for themselves, manage personal belongings, and follow school routines without constantly relying on the teacher. Teachers' strategies to support children's independence include using enjoyable methods such as songs, games, and direct practice, providing gradual assistance, giving positive reinforcement, and collaborating with parents and the school principal. The study concludes that health literacy implemented consistently in daily activities can serve as an effective strategy for training the independence of young children.